Solutions for Protecting Consumer Rights on E-commerce Platforms under Vietnamese Law (International Journal of Scientific Research and Management (IJSRM), 2024)
The Vietnamese legal framework for consumer protection in e-commerce transactions is still in the process of gradual improvement, with many limitations remaining. Violations of consumer rights frequently occur, causing damage to consumers when purchasing goods on e-commerce platforms. To promote the development of e-commerce transactions, it is necessary for the government to supplement legal regulations on consumer protection in e-commerce, ensuring the protection of consumers’ legitimate rights and fostering their confidence and sense of security when conducting transactions on these platforms. This article highlights the challenges faced by consumers on e-commerce platforms and proposes appropriate solutions to protect consumer rights in accordance with Vietnamese law.